Persepsi Sosial Terhadap Komodifikasi Tubuh Perempuan (Studi Kasus Sales Promotion Girl Di Mall Ratu Indah Makassar) - Rusni Hadji; Nurdin Nurdin; Lukman Ismail (Indonesian Journal Publisher, 2020)
Public spaces such as malls and entertainment venues have been visited by many people. This opportunity is used by industries engaged in the service sector to make a profit. Not a few agencies have created jobs to recruit employees in the field of promotional services. Promotion services work in the informal sector with the skills required by agencies to recruit women as sales promotions. SPG is used as a shortcut for some women to get a job. Women have a gentle attitude and are good at seducing with their physical capital, beautiful faces and eloquence in offering products to customers. SPG is used as the main job for women to make it easier to earn money. Most of the women who only go to school until they finish Senior High School (SMA) or Vocational High School (SMK) choose to work as SPGs. This job does not require high skills, only with a beautiful physique and face. This gives the view that the body and face are working capital as an SPG. The company benefits more from the SPG because it is seen as being able to boost product sales. In this study, the type of research used is a qualitative approach, namely